2014
DOI: 10.1371/journal.pone.0114841
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Binaural Cues Develops in Children Who Are Deaf through Bilateral Cochlear Implantation

Abstract: There are significant challenges to restoring binaural hearing to children who have been deaf from an early age. The uncoordinated and poor temporal information available from cochlear implants distorts perception of interaural timing differences normally important for sound localization and listening in noise. Moreover, binaural development can be compromised by bilateral and unilateral auditory deprivation. Here, we studied perception of both interaural level and timing differences in 79 children/adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 50 publications
10
54
1
Order By: Relevance
“…Moreover, children increasingly lateralized these sounds to one side of their head as BD amplitude increased. In later work, Gordon and colleagues found that perception of ILDs was established at very early stages of bilateral implant use even for children who were older and heard through one implant for most of their lives [34]. This was consistent with findings that most children are able to discriminate stimuli containing ILD cues when tested after longer periods of bilateral implant use [26, 35].…”
Section: Direct Stimulation Of Binaural Hearingsupporting
confidence: 56%
“…Moreover, children increasingly lateralized these sounds to one side of their head as BD amplitude increased. In later work, Gordon and colleagues found that perception of ILDs was established at very early stages of bilateral implant use even for children who were older and heard through one implant for most of their lives [34]. This was consistent with findings that most children are able to discriminate stimuli containing ILD cues when tested after longer periods of bilateral implant use [26, 35].…”
Section: Direct Stimulation Of Binaural Hearingsupporting
confidence: 56%
“…Future investigations focus on whether we can compensate for these large asymmetries in stimulation and neural conduction, and whether children using a CI and a hearing aid can develop a fused binaural image or obtain true binaural hearing. It may be that children require greater lengths of experience to use ITD and ILD cues, as we have seen in bilaterally deafened children with a long delay between receiving their two CI [Gordon et al, 2014]. These children were able to detect some ITD cues only after several years of using bilateral CI, although sensitivity remained abnormal.…”
Section: Discussionmentioning
confidence: 76%
“…75,94 Thus, even in the worst condition (early onset, long duration of single-sided deafness), there is some hope for stimulating hearing in the deaf ear and establishing binaural hearing, with demonstrable benefits already realized. 64-66,68-70, [131][132][133][134] On the other hand, these skills remain abnormal, reflecting persistent reorganization after single-sided hearing. Without focused training, 3 to 4 years of bilateral implant use was not sufficient to reduce the preference of the first-implanted ear…”
Section: Important Factors For a New Treatment Of Asymmetric Hearing mentioning
confidence: 99%
“…122 Although these children learned to detect large changes in binaural timing cues after long periods of bilateral implant experience, they continued to judge input as coming from the side of their first implant more often than children receiving bilateral implants simultaneously. 134 Furthermore, although speech perception was gained in the weaker ear, the progress was slow and did not match the stronger ear even after 5 to 9 years of implant use. 58 Poor speech perception 55 together with absent cortical binaural interaction 135 in children receiving the second implant as adolescents suggest that there are continued difficulties in processing input from the second-treated ear.…”
Section: Figurementioning
confidence: 99%